1995
DOI: 10.1007/bf02814729
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some spices as preservatives for storage of lentil (Lens esculenta L.) seeds

Abstract: The high antimycotic activity of four kinds of spices, viz, Chinese cassia, cinnamon, clove and thyme, were tested as preservatives for agricultural commodities. Clove, thyme and a mixture of the four kinds of spice completely inhibited aflatoxin production on lentil seeds during eight weeks of incubation. Chinese cassia and cinnamon partially inhibited the aflatoxin production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…This antifungal capacity of thyme essential oil has also been demonstrated by Montes and Carvajal (1998) and Basilico and Basilico (1999) on fungi such as A. flavus, Aspergillus parasiticus, Aspergillus ochraceus, Aspergillus fumigatus and Fusarium spp. Other authors, too, including El-Maraghy (1995) and Inouye et al (2000), confirmed these results. According to Soliman and Badeea (2002), this antifungal effect might be caused by the b-pinene content of thyme essential oil because it can reach values of 29.9-37.6%.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…This antifungal capacity of thyme essential oil has also been demonstrated by Montes and Carvajal (1998) and Basilico and Basilico (1999) on fungi such as A. flavus, Aspergillus parasiticus, Aspergillus ochraceus, Aspergillus fumigatus and Fusarium spp. Other authors, too, including El-Maraghy (1995) and Inouye et al (2000), confirmed these results. According to Soliman and Badeea (2002), this antifungal effect might be caused by the b-pinene content of thyme essential oil because it can reach values of 29.9-37.6%.…”
supporting
confidence: 57%
“…This antifungal capacity of thyme essential oil has also been demonstrated by Montes and Carvajal (1998) and Basilico and Basilico (1999) on fungi such as A. flavus , Aspergillus parasiticus , Aspergillus ochraceus , Aspergillus fumigatus and Fusarium spp. Other authors, too, including El‐Maraghy (1995) and Inouye et al . (2000), confirmed these results.…”
Section: Resultsmentioning
confidence: 93%
“…A wide spectrum of pharmacological activities have been described for thyme, such as antioxidant (13), antibacterial (26,27) and antifungal (28,29) properties. These activities have been attributed to some widely distributed species of thyme.…”
Section: Discussionmentioning
confidence: 99%
“…The antifungal activity of thyme, spearmint and basil was also demonstrated by Montes-Belmont and Carvajall (1998) and Basilico and Basilico (1999) on the toxigenic fungi Aspergillus flavus, Aspergillus parasiticus, Aspergillus ochraceus, Aspergillus fumigatus and Fusarium spp. The antifungal activity of mint, basil and thyme on some pathogenic fungi, including Aspergillus flavus and Aspergillus parasiticus has also been reported which suggested their inhibitory effects on the sporulation of fungi and aflatoxin production [Ela et al, 1996;Inouye et al, 1998;Inouye et al, 2000;El-Maraghy, 1995;Dube et al, 1989]. These effects could be related to several components known to have biological activities, such aspinene, -pinene in thyme, basil and spearmint, respectively.…”
Section: Interference Of Natural Products In Aflatoxin Biosynthesismentioning
confidence: 99%